Monocultures and Sustainability:: Analysis of Three Brazilian Regions - CASTRO, RAIFRAN ABIDIMAR DE; CASTRO, EDNA MARIA RAMOS DE (Sustainability in Debate, 2015)
The growing demand for biofuels and bioenergy widens the debate about monocultures and their sustainability. In this sense, the objective of this article is to present an analysis of the positive and negative aspects of the monocultures of eucalyptus, soybean and palm tree in three Brazilian regions, as well as their interconnections with sustainability issues. Altogether with a literature review, the chosen approach has been qualitative, with an emphasis on descriptive and explicative analyses. Results point out to the lack of understanding of the positive and negative aspects of the deployment of monocultures in the studied regions and their social, environmental and economic impact. All this challenges decision making by State agents, private entrepreneurs and the communities involved with these cultures.